Кубань: від української колонізації до її зросійщення. Спроба неупередженого аналізу - Коропатник, М. (Сiверянський лiтопис, 2019)
У статті, яка складається з трьох частин, розглядаються процеси колонізації
Кубані українцями – козаками й селянами від кінця ХVІІІ до початку ХХ ст., соціально-економічні та суспільно-політичні обставини, що визначали переселенську політику
російського царизму. Дається характеристика революційних подій 1917–1921 рр.
на території краю, у т. ч. стосовно створення та діяльності Кубанської Народної
Республіки, її зв'язків з УНР і Українською державою, подальшого розвитку ситуації в
радянську та пострадянську добу. The first part of the article deals with the processes of colonization of Kuban by
Ukrainians (Cossacks and peasants) from the late 18th century to the early 20th century,
and socioeconomic and sociopolitical circumstances that determined the resettlement policy
of Russian tsarism.
The task is to provide an objective analysis of exploration of Kuban by the Ukrainian
settlers, its positive and negative sides, the policy of using the Ukrainian factor in imperial
interests, as well as the difficult way of preserving Ukrainian identity using comparativehistorical,
historical-typological and historical-systematic research methods.
The period from 1775 until the end of the Caucasian War in 1864 was the time of
resettlement of hundreds of thousands of Ukrainian Cossacks and peasants to the North
Caucasus, and, in particular, to the Kuban, which was organized by the Tsarist Government.
However, this was also the desire of the Cossacks to assert their right to exist, and therefore
they asked Catherine II to give them the lands of Kuban for lifetime use. And this request
was approved with the imperial letter as of June 30, 1792.
The first waves of Cossack settlers were not massive. However, the settlement of Kuban
and some parts of the North Caucasus by Ukrainians has gradually become extensive. In
total, almost 159 thousand people, among whom were Cossacks as part of military formations,
former registered Cossacks and peasants, were resettled from Ukraine to Kuban during the
years 1792-1865. And before the Revolution of 1917, according to some scholars, population
of Ukrainians in Kuban made up 60% of the total population – 1791000 people.
One of the main reasons for the resettlement of Ukrainian Cossacks and peasants to
Kuban was the colonization and aggressive policy of the Russian Empire. The Ukrainian
Cossacks also had their motivation, so the attempts of the Tsarist Government to russify the
Black Sea Cossack did not have significant consequences. Among them, Ukrainian culture
prevailed. The Ukrainian language was perceived by the Cossacks as a certain sign of their
class origin and identity.